Is euro area money demand (still) stable? Cointegrated VAR versus single equation techniques - Ansgar Belke; Robert Czudaj (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this paper we present an empirically stable euro area money demand model. Using a sample period until 2009:2 shows that the current financial and economic crisis that started in 2007 does not appear to have any noticeable impact on the stability of the euro area money demand function. We also compare single equation methods like the ARDL approach, FM-OLS, CCR and DOLS with the commonly used cointegrated Johansen VAR framework and show that the former are under certain circumstances more appropriate than the latter. What is more, they deliver results that are more in line with the economic theory. Hence, FMOLS, CCR and DOLS are useful in estimating standard money demand as well, although they have only been rarely applied for this purpose in previous studies.
Keywords: C12; C22; C32; E41; E43; E58; 330; ARDL model; cointegration; euro area; financial crisis; money demand; Geldnachfrage; Europäische Wirtschafts- und Währungsunion; Finanzmarktkrise; Kointegration; Schätzung; EU-Staaten